2020
DOI: 10.3390/cancers12030724
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Circulating miR-483-5p Is a Prognosis Marker for Adrenocortical Cancer

Abstract: We have previously identified serum miR-483-5p as a preoperative diagnosis and prognosis biomarker for adrenocortical cancer (ACC). Here, we aimed to determine whether circulating miR-483-5p levels measured 3 months post-operatively distinguished patients with good prognosis (no recurrence for at least 3 years; NR3yrs) from patients with poor prognosis (recurrence or death within 3 years after surgery; R < 3yrs). We conducted a single-center retrospective analysis using sera from 48 patients with ACC that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…High circulating levels of miR-483-5p or low circulating levels of miR-195 are associated with both shorter recurrence-free survival and shorter overall survival in ACC [ 184 ]. Serum miR-483-5p levels measured 3 months after surgical procedure were, for example, higher in those with recurrence disease or lethal outcome within three years than in those without [ 185 ]. Receiver operating characteristic analysis showed that a value of 752,898 copies/mL was a cut off value to prognosticate recurrence with 61.5% sensitivity and 100% specificity [ 185 ].…”
Section: Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…High circulating levels of miR-483-5p or low circulating levels of miR-195 are associated with both shorter recurrence-free survival and shorter overall survival in ACC [ 184 ]. Serum miR-483-5p levels measured 3 months after surgical procedure were, for example, higher in those with recurrence disease or lethal outcome within three years than in those without [ 185 ]. Receiver operating characteristic analysis showed that a value of 752,898 copies/mL was a cut off value to prognosticate recurrence with 61.5% sensitivity and 100% specificity [ 185 ].…”
Section: Genetic Analysismentioning
confidence: 99%
“…Serum miR-483-5p levels measured 3 months after surgical procedure were, for example, higher in those with recurrence disease or lethal outcome within three years than in those without [ 185 ]. Receiver operating characteristic analysis showed that a value of 752,898 copies/mL was a cut off value to prognosticate recurrence with 61.5% sensitivity and 100% specificity [ 185 ]. Beside circulating miR-483-5p, its urinary counterpart has been evaluated in patients with adrenal tumors [ 186 ].…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming the previously reported data ( 42 44 ), MIR483 , located on intron 2 of the IGF2 locus, is overexpressed in ACC. Interestingly, a recent single-institution study of 48 patients suggested that mIR-483-5p measured after initial surgery for ACC can be a potential early post-operative biomarker for ACC prognosis to predict recurrence-free survival ( 45 ). In the ENSAT cohort, miRNA analysis revealed the upregulation of 11 miRNAs belonging to the miRNA-506-514 cluster (Xq27.3) and downregulation of 38 miRNAs to the imprinted DLK1-MEG3 cluster (14q32.2).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…Four articles report the results of explorative studies on the prognostic role of the counts of two tissue markers: sterol-O-acyl transferase 1 (SOAT1) [ 10 ] and CD8+-cytotoxic T lymphocyte [ 11 ], the latter being assessed in a pediatric series. Two blood parameters were also assessed in the form of circulating tumor cells [ 12 ] and miR-483-5p [ 13 ]. Another paper showed that a pervasive circulating autoantibody response against the cancer testis antigen FATE1—which is detected both in pediatric and adult ACC patients—is negatively correlated to disease-free survival (DFS) and overall survival (OS) in adult patients and is associated with decreased immune response-associated gene expression [ 14 ].…”
mentioning
confidence: 99%